1994
DOI: 10.1111/j.1365-3040.1994.tb02007.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling forest response to increasing CO2 concentration under nutrient‐limited conditions

Abstract: The growth rates of woody plants depend on both the rate of photosynthetic carbon gain and the availability of essential nutrients. Instantaneous carbon gain is known to increase in response to increasing atmospheric CO2 concentration, but it is uncertain whether this will translate into increased growth in the longer term under nutrient‐limited conditions. An analytical model to address this question was developed by Comins & McMurtrie (1993, Ecological Applications 3, 666–681). Their model was further tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 88 publications
3
100
0
Order By: Relevance
“…We suggest therefore that the increased net photosynthetic carbon gain resulting from COg enrichment (see Barnes et al, 1995a) might have been reflected in a substantially increased rate of carbon input into the rhizosphere, which, combined with an increase in root size (Pfirrmann, 1992), stimulated microbial activity and increased CECeff. It remains to be established whether similar effects occur in the field in response to prolonged CO2 enrichment because longer-term exposure to elevated CO2 has been shown to increase the C/N ratio of litter through increases in carbon-based secondary compounds such as lignin and tannins (Eajer, Bowers & Bazzaz, 1992), and this might reduce decomposition and nitrogen mineralization processes, leading to a progressive immobilization of nutrients in the soil (Kirschbaum et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest therefore that the increased net photosynthetic carbon gain resulting from COg enrichment (see Barnes et al, 1995a) might have been reflected in a substantially increased rate of carbon input into the rhizosphere, which, combined with an increase in root size (Pfirrmann, 1992), stimulated microbial activity and increased CECeff. It remains to be established whether similar effects occur in the field in response to prolonged CO2 enrichment because longer-term exposure to elevated CO2 has been shown to increase the C/N ratio of litter through increases in carbon-based secondary compounds such as lignin and tannins (Eajer, Bowers & Bazzaz, 1992), and this might reduce decomposition and nitrogen mineralization processes, leading to a progressive immobilization of nutrients in the soil (Kirschbaum et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is growing recognition that this response can only be sustained where other resources, particularly nutrients, are available to support the extra growth induced by CO2 enrichment (Kirschbaum et al, 1994;Gundersson & Wullschleger, 1994;Petterson & McDonald, 1994;Barnes et al, 1995a). One factor influencing the nutrient content of tree foliage is the rate at which cations are leached from the canopy (Tukey, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…However, most models are still sensitive to key input parameters and assumptions, so that sensitivity analysis of model outcomes must be made to indicate the probability range of the predictions. One ecosystem model suggests that increases in tree C storage under elevated CO # might eventually be reduced through nutrient limitations if N is stored in pools of slow turnover such as wood (Kirschbaum et al, 1994). However, Thornley & Cannell's (1996) model suggested that coniferous forests increase N acquisition in response to elevated CO # and hence sustain increased net primary productivity despite decreasing N supply and\or leaf area index.…”
Section: Modelling Effects On a Regional Scalementioning
confidence: 99%
“…Models incorporating the effects of elevated CO # on production or ecosystem physiology have increased greatly in complexity and realism since a previous review (Long & Hinchin, 1991), and it is now possible to employ experimental results from plantlevel studies toward estimating regional and global processes in a future, higher CO # environment (Kirschbaum et al, 1994 ;Woodward, Smith & Emmanuel, 1995) with appropriate scaling (Jarvis, 1995). However, most models are still sensitive to key input parameters and assumptions, so that sensitivity analysis of model outcomes must be made to indicate the probability range of the predictions.…”
Section: Modelling Effects On a Regional Scalementioning
confidence: 99%
“…For example, although the model has often been used to estimate effects of elevated atmospheric [CO 2 ] (C a ) on canopy performance (e.g. Kirschbaum et al, 1994;Medlyn, 1996;Kruijt et al, 1999;Luo et al, 2001), the model cannot be used to investigate elevated [CO 2 ] impacts in drought conditions because it is not possible to calculate how elevated [CO 2 ] modifies soil moisture.…”
Section: Introductionmentioning
confidence: 99%